Correlates of physical activity and sedentary behaviour in children attending before and after school care: a systematic review - Andrew J. Woods; Yasmine C. Probst; Jennifer Norman; Karen Wardle; Sarah T. Ryan; Linda Patel; Ruth K. Crowe; Anthony D. Okely (BMC, 2022)
Abstract Background Out of School Hours Care (OSHC) offers structured care to elementary/primary-aged children before and after school, and during school holidays. The promotion of physical activity in OSHC is important for childhood obesity prevention. The aim of this systematic review was to identify correlates of objectively measured physical activity and sedentary behaviour in before and after school care. Methods A systematic search was conducted in Scopus, ERIC, MEDLINE (EBSCO), PsycINFO and Web of Science databases up to December 2021. Study inclusion criteria were: written in English; from a peer-reviewed journal; data from a centre-based before and/or after school care service; children with a mean age < 13 years; an objective measure of physical activity or sedentary behaviour; reported correlations and significance levels; and if an intervention study design these correlates were reported at baseline. Study quality was assessed using the Office of Health Assessment and Translation Risk of Bias Rating Tool for Human and Animal Studies. The PRISMA guidelines informed the reporting, and data were synthesised according to shared correlations and a social ecological framework. Results Database searches identified 4559 papers, with 18 cross-sectional studies meeting the inclusion criteria.There were a total of 116 physical activity correlates and 64 sedentary behaviour correlates identified. The most frequently reported correlates of physical activity were child sex (males more active), staff engaging in physical activity, an absence of elimination games, and scheduling physical activity in daily programming (all more positively associated). The most frequently reported correlates of sedentary behaviour were child sex (females more sedentary) and age (older children more sedentary). Conclusions Encouraging physical activity engagement of female children, promoting positive staff behaviours, removing elimination elements from games, and scheduling more time for physical activity should be priorities for service providers. Additional research is needed in before school care services.